La motricidad fina y su incidencia en la correcta escritura en los estudiantes de tercer año paralelo “b” de educación general básica del área de lengua y literatura de la escuela “Luis Aurelio González” cantón Guaranda, provincia Bolívar, en el período 2021-2022 - Narvaez Jiménez, Max Fabricio (2022)
Basic Education is considered the mother of all sciences because from it human beings emerge and are formed with values, responsibilities, emphasizing projecting good individuals for society. Their proper development and development in the society that surrounds them will depend on their correct academic education. Therefore, it has been, is and will be vital to take into account the problems and interferences that arise in the correct educational development of students, even more so when they persist. In our country, despite the fact that education has improved by leaps and bounds, it is clear that there are still significant mishaps that, although they have been dealt with, persist for different reasons and/or events that occur in the course of educational processes. One of the fields in which students present educational problems is when exercising their correct writing skills, because they do not carry out and/or practice adequately the activities proposed by their teachers or parents, who generally they leave all responsibility for their children's learning in the hands of the teacher, arguing that this is why they send them to an educational institution. That is why we, the researchers, as students in professional academic training of the Basic Education career, during the eight academic cycles, in the framework of pre- professional practices, it was possible to demonstrate and analyze a great problem that, without wanting is unfortunately developed in the formation of students. Therefore, having to carry out our degree project or Curriculum Integration Unit, in order to obtain a Bachelor's degree in Basic Education, the research team has considered it appropriate to inquire about fine motor skills and its impact on correct 12 writing in Third year parallel "B" students of Basic General Education in the Language and Literature area of the "Luis Aurelio Gonzales" School, Guaranda Canton, Bolívar province, in the period 2021-2022. By virtue of the silver theme, together with the timely and necessary advice from our tutor, he proceeded to execute the investigation with its respective steps in order to prepare and comply with all the requirements that compete with it. Subsequently, the respective antecedents were carried out, which have their respective levels, both macro in consideration of our country, of a meso nature in reference to the province of Bolívar and of a micro nature in reference to the educational institution, based on the knowledge acquired during our university academic training. On the other hand, the problem in question, its description and formulation are based. Next, we continued with the respective justification of our inquiry, which has its due importance, necessity, benefits, scientific novelty and, above all, its authenticity and/or originality of the project. In the same circumstances, the objectives were crystallized, which allowed us to be clear about what we want to achieve and where to go, starting with a general objective and later with specific objectives. Consequently, we saw the need to carry out the scientific theory in reference to the two variables of our research, both fine motor skills and correct writing. Once the previous step was completed, we proceeded to investigate the articles related to education and especially to our research topic in order to support it through the articles established by the constitution of the Republic of Ecuador. Opportunely to develop the referential theory, it was possible to obtain it thanks to the opening of the rector of the institution, who had key and original information to support our inquiry. Of equal importance, the steps of the methodological framework, its data collection techniques and instruments, its population, information process and later the analysis and interpretation of data in a quantitative way for the students and qualitatively for the teacher were fulfilled; therefore, the ability to conclude objectively-cognitively was obtained. Finally, in consideration of what was obtained and exposed about fine motor skills and their impact on correct writing, we saw the need to make a novel proposal for the students involved called "Fine motor strategies to improve writing in children of third grade of Basic Education